From poverty to health: intraurban inequalities in child health indicators in low-income and middle-income countries during the SDG era - Amanuel Yosef Gebrekidan; Yordanos Sisay Asgedom; Tsion Mulat Tebeje; Mesfin Abebe; Mekonnen Birhanie Aregu (BMJ Global Health)
Introduction Urban areas are generally associated with better health outcomes. However, in many low-income and middle-income countries (LMICs), rapid urbanisation has led to significant health disparities. These inequalities, especially those affecting the urban poor, are often overlooked in studies focused solely on rural–urban differences. This study aimed to assess the overall and country-specific intraurban inequalities in under-5 and neonatal mortality rates, immunisation coverage, care-seeking for acute respiratory infections (ARIs), coverage of diarrhoea treatment, and stunting, wasting and overweight in children under 5.Methods Demographic and Health Survey datasets collected since 2015 from 48 LMICs were analysed. We constructed an urban poor cluster using the United Nations Human Settlements Programme definition for slums and categorised them as urban poor and urban non-poor clusters. The Wagstaff normalised concentration index (WCI) and concentration curve were used to assess urban poverty-related inequalities in child health indicators.Results In LMICs, 13.7% (95% CI: 13.6% to 13.9%) of urban children lived in poor clusters, with over 65% of urban clusters classified as poor in Chad, Ethiopia and Afghanistan. All child health indicators, except neonatal mortality, exhibited significant inequality between the urban poor and non-poor. Despite some inconsistencies across countries, there were pro-urban poor inequalities in under-5 mortality (WCI=−0.069), stunting (WCI=−0.121) and wasting (WCI=−0.088). Full vaccination coverage (WCI=0.078), overweight (WCI=0.087), care-seeking for children with acute respiratory infections (WCI=0.131) and receiving oral rehydration salts and zinc for diarrhoea (WCI=0.127) showed pro-urban non-poor inequality in LMICs.Conclusions Substantial intraurban inequalities were observed in child health indicators. Under-5 mortality, stunting and wasting were concentrated among urban poor children, while health service utilisation and overweight were concentrated among urban non-poor children. Improving access to clean water, sanitation, quality healthcare and education in underserved urban areas, along with combating urban poverty and promoting healthy lifestyles, is essential for achieving better health outcomes.